El gobierno insurgente en Oaxaca, 1812-1813 - Jiménez Lescas, Raúl Javier (Universidad Michoacana de San Nicolás de Hidalgo, 2015)
One of the summits Works of Joseph Maria Morelos y Pavon and the insurgent army and was called Expedition to Oaxaca and the insurgent creole government that flourished between in 1812-1813. A military work than continued the successful breaking of great Huajuapan Site (the most durable and long War of Independence) but also of political, religious and social character. Morelos in Oaxaca showed his statesmanship. In Oaxaca emanate the idea of convening a congress called insurgents of Anahuac (Chilpancingo). After 3 centuries of Spanish imperial domination, a brief creole insurgent government, which over the years would have political and cultural changes in Oaxaca.

Una de las obras cumbres de José María Morelos y Pavón y el ejército insurgente fue la ?Expedición a Oaxaca? y el gobierno criollo insurgente que floreció entre 1812 y 1813. Una obra militar que continuó la exitosa ruptura del ejemplar Sitio de Huajuapan (el más largo de la Guerra de Independencia) pero también de carácter político, religioso y social. Morelos mostró sus dotes de estadista y, de ahí saldría el V Vocal de la Suprema Junta Americana, José María Murguía y Galardi, así como la idea de convocar a un congreso que los insurgentes llamaron de Anáhuac (Chilpancingo). Después de tres siglos de dominación imperial, un breve gobierno insurgente, que con el paso de los años tendría cambios en Oaxaca.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; FH-M-2015-0172; Opción en historia regional continental; Insurgencia; Antequera; Oaxaca; Contrainsurgencia; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/277